1998
DOI: 10.1126/science.279.5357.1676
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Field and Plasma Observations at Mars: Initial Results of the Mars Global Surveyor Mission

Abstract: The magnetometer and electron reflectometer investigation (MAG/ER) on the Mars Global Surveyor spacecraft has obtained magnetic field and plasma observations throughout the near-Mars environment, from beyond the influence of Mars to just above the surface (at an altitude of ∼100 kilometers). The solar wind interaction with Mars is in many ways similar to that at Venus and at an active comet, that is, primarily an ionospheric-atmospheric interaction. No significant planetary magnetic field of global scale has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
193
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 687 publications
(194 citation statements)
references
References 34 publications
(16 reference statements)
0
193
0
1
Order By: Relevance
“…a weakly magnetized celestial body with atmosphere and ionosphere exposed to a superAlfvénic plasma flow [e.g., Alfvén, 1953]. The Mars Global Surveyor (MGS) findings of strong crustal anomalies at Mars [Acuña et al, 1998] considerably changed this picture. We now expect to find diverging magnetic field "cusps" above Mars [Krymskii et al, 2002] and "minimagnetospheres" [Mitchell et al, 2001] with local magnetic conditions similar to those found on magnetized planets such as the Earth.…”
Section: Introductionmentioning
confidence: 99%
“…a weakly magnetized celestial body with atmosphere and ionosphere exposed to a superAlfvénic plasma flow [e.g., Alfvén, 1953]. The Mars Global Surveyor (MGS) findings of strong crustal anomalies at Mars [Acuña et al, 1998] considerably changed this picture. We now expect to find diverging magnetic field "cusps" above Mars [Krymskii et al, 2002] and "minimagnetospheres" [Mitchell et al, 2001] with local magnetic conditions similar to those found on magnetized planets such as the Earth.…”
Section: Introductionmentioning
confidence: 99%
“…Among other important results, the measurements made by the magnetometer (MAG) on board the Mars Global Surveyor (MGS) spacecraft [Acuña et al, 1992] showed that Mars does not have a significant intrinsic magnetic field [Acuña et al, 1998]. As a consequence, there is a direct interaction between the magnetized solar wind (SW) and the atmosphere/ionosphere of the planet.…”
Section: Introductionmentioning
confidence: 99%
“…Cloutier et al, 1999), also lacking a global planetary magnetic field (e.g. Acuña et al, 1998). A statistical study of low-frequency magnetic field oscillations in the Martian plasma environment is presented by Espley et al (2004).…”
mentioning
confidence: 99%